Nonirritant and Cytocompatible Tinospora cordifolia Nanoparticles for Topical Antioxidant Treatments - González-Masís, Jeimmy; Cubero-Sesin, Jorge M.; Corrales-Ureña, Yendry Regina; González-Camacho, Sara; Mora-Ugalde, Nohelia; Vega-Baudrit, José Roberto; Rischka, Klaus; Verma, Virendra; Gonzalez-Paz, Rodolfo J. (International Journal of Biomaterials, 2020)
Tinospora cordifolia extract contains antioxidants such as polyphenols, and thus, it has been used as a natural phytochemical antioxidant therapeutic agent. Many of these compounds are insoluble or only partially soluble in water. In this study, we produced a novel aqueous nanoparticle formulation, with an average particle size of 182.9 ± 3.8 nm, to improve the dispersion of the bioactive compounds in water and to increment its bioavailability. The nanoparticles are composed of polyphenols, alkaloids, and glycosides. We studied the effect of this nanoparticle formulation on mouse 3T3 fibroblast cell viability and New Zealand rabbit dermal irritability tests. Concentrations of 2.5, 25, and 250 µg/mL resulted in similar cell viability to cells in culture media. An intermediate concentration of 12.45 mg/ml was used for the acute dermal irritability test. There were no severe alterations that compromised animal health. These results represent a precedent for application of such nanoparticles derived from plant stems, such as Tinospora cordifolia, in biomedicine and in antiaging cosmetic treatments.